Predation risk increases intraspecific heterogeneity in white-tailed deer diel activity patterns. (9th November 2020) - Crawford, Daniel A; Conner, L Mike; Morris, Gail; Cherry, Michael J
Abstract: Prey species often mitigate predation risk through alteration of spatiotemporal diel activity patterns whereby prey access high-quality resources in risky areas during predator downtimes. However, dominance hierarchies exist in some prey species, and temporal partitioning is a mechanism thought to reduce aggressive intraspecific interactions. How demographic-specific responses to predation risk influence intraspecific temporal partitioning in prey are largely unknown and could be key to understanding the effects of predators on intraspecific interactions in prey. To assess the effects of predation risk on intraspecific interactions in white-tailed deer ( Odocoileus virginianus ), we monitored deer diel activity during the fawning season in four pairs of predator exclusion and control plots (~40 ha) from 2015 to 2018 using 16 camera traps. We examined the effect of predation risk on diel activity of males, females, and nursery groups by comparing the within-group coefficient of activity overlap (d̂) across predator exclusion and control plots. We then examined within-treatment activity overlap between groups in the predator exclosure and control plots. All groups maintained different diel activity patterns in safe and risky areas. Unconstrained by predation risk, all groups behaved more similarly, and interspecific group overlap was greater in the predator exclusion plots than control plots. Male-nursery group overlap exhibited the strongest treatment effect, increasing 24% in predator exclusion plots (d̂ = 0.91, confidence interval [CI]: 0.87–0.95) relative to control plots (d̂ = 0.67, CI: 0.57–0.76). Our results suggest predators increase heterogeneity in prey behavior and may be important drivers of behavioral processes, such as temporal partitioning, that minimize antagonistic intraspecific interactions of prey. Abstract : Fear of predators mediates prey behavior and is thought to play a causal role in sexual segregation of ungulate species. We experimentally manipulated predation risk for white-tailed deer using predator exclusion. We found that, in the absence of predation, males, females, and nursery groups behaved more similarly, and predation risk decreased intraspecific diel activity overlap. Our results suggest predation risk increases behavioral heterogeneity in prey as demographic groups have variable mortality risk, risk tolerances, and ultimately antipredator responses.